PENCEGAHAN STUNTING DI DESA DAYEUHMANGGUNG - Rezeki, Pamella M Sri; Fadhilah, Rizal Ahmad; Shiddiq, Muhammad Jafar; Rahmawati, Siti Saadah; Cahya, Meisya Aura; Fatra, Salman Dial; Sidqi, Iqbal; Sahid, Ahmad Nur; Ramadhan, Muhammad Renaldy Taufiq; Putra, Andika Eka Sastya; Hafitri, Agisni Maulani; Nurdin, Ihsan; Taufik, Muhammad Irwan; Putri, Fujiyanti Rifani; Mukhlis, Ade; Pamungkas, Lutfi Berlian Putra; Prasetyo, Nurcholis Ade; Putra, Gelar Satria; Anisa, Hani Nur; Furkon, Furkon; Mubarok, Ahmad Hilal (Institut Teknologi Garut, 2024)
Prevention of Stunting in Dayeuh Manggung VillageStunting is a health issue that is often experienced by children in Dayeuhmanggung Village. This is due to a lack of access to balanced nutrition and adequate sanitation. The issue can be addressed through community service activities in the form of seminars that have been conducted with the aim of raising awareness and knowledge among the public regarding the importance of balanced nutrition, good eating habits, and hygiene to prevent infections. The method used in this service is the Work Breakdown Structure (WBS) scheme, which breaks down the work process into smaller parts to facilitate planning and coordination. The results of the seminar activities indicate an increase in public understanding of stunting and its prevention measures, as well as the participants' ability to apply the knowledge gained in their daily lives. Support from the government, health organizations, and active community participation also strengthens the positive impact of this activity. A systematic and collaborative approach is expected to address the stunting cases in Dayeuhmanggung Village.